A lot streaming based flow shop scheduling problem using simulated annealing algorithm. (2021) - Ramesh, C.; Kamalakannan, R.; Karthik, R.; Pavin, C.; Dhivaharan, S.
Abstract: This paper studies and attempts to present the challenge of allocation of resources in the n jobs – m machines flow shop scheduling background. In this arrangement, lot streaming is a technique used to segregate several sublots to permit tasks to connection transversely many manufacturing systems. The intention of this effort is to diminish the instance and saving the built-up cost. In current time, investigators have used intelligent heuristics to explicate flow shop difficulty on a lot streaming dilemma. In this effort, Simulated Annealing algorithm is used to resolve the lot streaming idea in the flow shop setting up with the goal of reducing the makespan time. The outcome obtained by this algorithm is evaluated with the standard benchmark instances. This planned algorithm is proficient and institute to be a better-quality problem solving technique for this flow shop scheduling with lot streaming. The algorithms are evaluated by means of Baker's algorithm for 2 m/c cases and the makes pan criterion, which shows the capability of it.